Illicit drug use patterns among hospitalized patients after the covid-19 pandemic and economic crisis - Tanrıkulu, Ali Baran; Koçhan, Onur (Journal of Dependence, 2024)
Objective: This study aimed to investigate the impact of the COVID-19 pandemic and subsequent economic crisis on illicit drug use patterns in Türkiye. Method: The study population comprised 1027 patients diagnosed with substance use disorder (SUD). 615 patients who were hospitalized between May 2018-December 2019 and 412 patients who were hospitalized between December 2021-August 2023 at the Alcohol-Drug Addiction Research, Treatment and Training Center in Elazığ Mental Health and Diseases Hospital were recruited to study. Results: The rate of opioid-positive results was significantly higher in the May 2018-December 2019 group. The rate of methamphetamine-positive results was significantly higher in the December 2021 - August 2023 group. The rate of cannabis-positive results was found to be similar between the two groups. The treatment completion rate was significantly lower in methamphetamine-positive patients when compared with methamphetamine-negative patients. The treatment completion rate was significantly higher in opioid-positive patients when compared with opioid-negative patients. Discussion: While methamphetamine consumption has significantly increased, opioid consumption has significantly decreased in the wake of the economic crisis in Türkiye and the COVID-19 pandemic. Monitoring changes in illicit drug use patterns could help take appropriate measures.